REQUIREMENTS FOR TEACHERS IN ENSURING THE EFFECTIVENESS OF PRESCHOOL EDUCATION - M.N.Xushnazarova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is based on the comprehensive in-depth pedagogical and psychological preparation of educators in ensuring the effectiveness of preschool education, the requirement of each educator to have a clear knowledge of the specific aspects. It also covers the issues of the formation of the necessary skills and imagination in the students about what requirements each educator must comply with when drawing up his personal plan.